(untitled) (Texas Journal of Engineering and Technology, 2023)
This article is one of the main links of decision economics effective from the soils and land resources that are the basis of agriculture walking, organizing regular productivity control activities And it is designed to be applied in practice, and GIS technologies are described in detail made, unused GIS and their adjustment, computer cartographic data methods of collection, storage, processing, representation of soil science topics in GIS and review production such as production production based on their database. In my research work, geoinformation systems and technology in soil science dedicated to the development of fast modern information technologies the role of the document in learning is considered. Spatially distributed data, the most popular GIS is a general product of production and supply, data collection and updating procedures, their processing, soil science and transplanting from the ground store and use, get them. Internet and mobile systems, in GIS dispatch from remote sensing data. GIS in Sustainable Place Management application of technologies is considered in depth.